الفطريات المرافقة لحبوب الذرة الصفراء المخزونة وتقصي تلوثها بالسموم الفطرية المنتجة من الفطر (Sacc.)Fusariumverticillioides - الدخيل, حسين; العرفي, أيمن; ثلاج, يارا (Latakia University Journal -Biological Sciences Series, 2017)
هدفت هذه الدراسة إلى إجراء مسح للفطريات المرافقة لحبوب الذرة الصفراء المخزونة من العروة الخريفية في الموسم2011، والتركيز على الفطر Fusariumverticillioides، والكشف بالتحليل الكيميائي على السموم(FUM)Fumonisinوzearalenone(ZEA) المنتجة من قبل الفطر F.verticilloides تم ذلك في ثلاثة مواقع لاستلام وتخزين الحبوب (دير الزور والرقة والحسكة). أظهرت النتائج تلوث حبوب الذرة الصفراء بنسب 28.9، 32.5 و36.4%، ونسب رطوبة الحبوب 14.3، 17.2 و18.5% على التوالي في محافظات الحسكة، دير الزور والرقة. تم التعرف على 6 أجناس فطرية مرافقة للحبوب الملوثة بنسب مئوية متفاوتة وكانت المتوسطات في المحافظات الثلاثة بالترتيب Penicillium(40.2%)، Aspergillus(37.4%)،Fusarium (12.6%)،Rhizopus(4.5%)، Mucor (3.8%) وAlternaria(1.4%). كما تبين سيادة النوع F. verticillioidesمن بين أنواع الفطرFusariumspp.بمتوسطات بلغت 83.8، 78.9 و82.0% على التوالي للمحافظات الثلاث، وتراوحت كمية السم FUM(0.6 -5.3)، (0.9 – 6.7) و(0.2 -2.3) ملغ/كغ، في حين تراوحت كمية السم (ZEA)بين (0.2-2.1)، (0.5-7.6) و(0.03-0.8) ملغ/كغ على التوالي في محافظات دير الزور، الرقة والحسكة. وتبين التحاليل بوساطة الكروماتوغرافيا أن 42 عزلة من أصل 60 عزلة من F. verticillioidesتمتلك قابلية إنتاج السم (FUM) بنسب بلغت 70%، 80% و60% في المحافظات الثلاثة.This study was carried out to survey the mycoflora of maize grain stored in the autumn season in 2011. Special attention to was paid to Fusariumverticillioides and detection of chemical analysis on the toxins Fumonisin(FUM) and zearalenone (ZEA) produced from F.verticilloides in three locations for the receipt and storage of grain in Deirezzor and Raqqa and Hasaka. The results showed that maize kernels discolored in rate of between 28.9, 32.5 and 36.4% respectively in Hasaka, Deirezzor and Raqqa. There was a positive coloration between maize kernels discolored and grain moisture percent. Microbial analysis showed associated fungi were Penicillium spp. (40.2%), Aspergillus spp. (37.4%), Fusariumspp. (12.6%), Rhizopus spp. (4.5%), Mucor spp. (3.8%) and Alternaria spp. (1.4%). F. verticillioides was the most frequency of Fusarium spp. Rates 83.8, 78.9 and 82.0% respectively in Deirezzor, Raqqa and Hasaka.Toxins (FUM) in Deirezzor was between 0.6 -5.3 mg / kg, and between 0.9 - 6.7 mg / kg in Raqqa, and from 0.2 to -2.3 mg / kg in Hasaka, while Toxins (ZEA) were between 0.2-2.1, -0.5 7.6 and 0.03-0.8 mg / kg respectively in the three locations.Chromatographic analysis showed that the isolation of 42 out of 60 isolates of F. verticillioides was producing Toxins (FUM), were more isolates producing isolates Raqqa by 80%, in Deirezzor 70% and 60%. In Hasaka.